2012
DOI: 10.1002/pola.26206
|View full text |Cite
|
Sign up to set email alerts
|

A phase‐separable second‐generation hoveyda‐grubbs catalyst for ring‐opening metathesis polymerization

Abstract: Polyisobutylene‐supported second‐generation Hoveyda‐Grubbs catalyst is shown to be an effective nonpolar phase tag for ring‐opening metathesis polymerization (ROMP). The catalytic activities of the supported Ru–carbene complex in ROMP are comparable to those of their homogeneous counterparts. The separability of these catalysts leads to lower Ru contamination (0.5 ppm levels) in the polymer products in comparison to the nonsupported Hoveyda‐Grubbs catalyst (10 PPM). © 2012 Wiley Periodicals, Inc. J Polym Sci P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…We have already showed that PIB-supported Ru complex 8 is useful in RCM 51 and ROMP of several substituted oxanorbornenes. 52 We report the results of our initial studies for the ROMP of cyclopentene M4, by exploring the feasibility of using a soluble polymer-bound Ru catalyst. The ROMP of strained cyclic olefins is mainly enthalpy-driven.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already showed that PIB-supported Ru complex 8 is useful in RCM 51 and ROMP of several substituted oxanorbornenes. 52 We report the results of our initial studies for the ROMP of cyclopentene M4, by exploring the feasibility of using a soluble polymer-bound Ru catalyst. The ROMP of strained cyclic olefins is mainly enthalpy-driven.…”
Section: Resultsmentioning
confidence: 99%
“…[54,55] PIB Ru complex 8 was prepared by following previously published protocols. [52] The catalytic activity of complexes HG2 and 8 were evaluated for the equilibrium ROMP of monomer M4 at two different temperatures. In all cases, the reaction was performed in THF under an inert atmosphere,u sing 0.225 mol %c atalyst loading for 60 min to furnish polymer P4 ( Table 1, Ta ble 1s ummarizest he conversion for ROMPo fm onomer M4;t he molecular weight distribution and the polydispersity index (PDI) of the polymers were determined by using gel permeationc hromatography (GPC) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…While there have been many reports documenting the ROMP of norbornene derivatives, there are surprisingly few examples of ROMP of low‐strain cyclic olefins using ruthenium catalysts. For example, Grubbs and coworkers reported the ROMP of cyclopentene and cycloheptene, the ROMP of cis , cis ‐cycloocta‐1, 5‐diene (COD), and ROMP of hydroxyl‐ or acetate‐disubstituted cyclopentene .…”
Section: Introductionmentioning
confidence: 99%
“…[40,[77][78][79][80][81] The concept of using soluble polymers for their phase-selective solubility, pioneered by Bergbreiter, [82][83][84][85] has attracted several research groups' attention, describing various polymer-tagged organometallic complexes to date in the literature. [86][87][88][89][90][91][92][93][94][95][96][97][98] The primary significance of tagging relies on the aforementioned phenomenon, i.e., the complexes became selectively soluble in the heptane phase of a biphasic heptane/ polar solvent mixture, facilitating the separation (in some cases the recycling) of the employed catalyst/complex. [91] The emergence of highly apolar long chain-anchored ligand-containing palladium complexes in the literature is limited.…”
Section: Doi: 101002/marc201700214mentioning
confidence: 99%